(untitled) (Journal Of Educational and Psychological Researches, 2022)
This study aims to identify the impact of social support on breast cancer patients’ psychological rigidity using a sample in Ramallah and al-Bireh. A descriptive correlative approach was adopted to fulfill the goals of the study and a questionnaire consisted of two criteria: social support and psychological rigidity, which was adopted as a tool for data collection for the study. In order to achieve the goals of the study, the researcher selected a convenient sample that consisted of 123 female breast cancer patients in Ramallah and al-Bireh. This sample represented 50% of the original patient population. The study showed that the average estimated percentage of social support and psychological rigidity for women with breast cancer, in the designated area, was elevated to up to 82.4% and 74.8% respectively. These results revealed a positive relationship between social support and breast cancer patients’ psychological rigidity. The resilience and stress management with the predictability of 0.412. There is a statistically significant difference for social support in regards to age, and social status. However, this was not observed with other factors namely: educational status, income, and disease duration. Statistically significant differences for psychological rigidity were observed with variations in age, social status, and disease duration, but not in terms of educational status and income. Considering these results, the researcher recommends the establishment of support programs that target women with breast cancer. Such programs would provide the patients with the required social and psychological care and spread awareness among patients. Thus, they can cope with the stress associated with breast cancer and comorbidities.